Implementasi Mata Kuliah Modul Nusantara terhadap Interaksi Sosial pada Program Pertukaran Mahasiswa Merdeka - Salsabilla Retno Sedah Mirah Murcahyaningrum; Nanang Martono; Wiman Rizkidarajat; Arif Darmawan; Edy Suyanto; Tri Rini Widyastuti (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study was to describe the implementation of the archipelago module course on social interaction in the independent student exchange activity program. This study used descriptive qualitative method. The subjects of this study were all students in the independent student exchange program at the University of Mataram. The results of the study show that this activity has a positive impact on social interaction, namely: Increasing understanding and appreciation of Indonesia's cultural diversity, improving communication skills, opening job opportunities, and increasing self-confidence. Constraints during implementation include Lack of qualified teaching staff, limited facilities and infrastructure, difficult access to resources, differences in student backgrounds, lack of support and attention from the campus. The conclusion of this study is that the implementation of the Independent Student Exchange Program has a positive impact on social interaction between students. Meanwhile, in overcoming the obstacles faced, cooperation is needed between all parties involved in this program, be it the campus, teaching staff, or students. Keywords: Implementation, Nusantara Module, Social interaction